PENGARUH KETERLIBATAN KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN (PT. SEGER AGRO NUSANTARA CABANG DOMPU) - Aris Munandar; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSRACTThis study aims to determine the effect of job involvement and job satisfaction on employee turnover intention. The sample of research in this study amounted to 50 people who are employees of PT. Seger Agro Nusantara Dompu Branch.The method used is descriptive data analysis using validity test, reliability, normality, multiple linear regression analysis, multicolinearity test, heterocedasticity test, hypothesis t test, and hypothesis test f.The results of this study indicate that partially each variable of work involvement and job satisfaction have a positive effect on turnover intention, while simultaneously work involvement variable and job satisfaction also have a positive effect on employee intention turnover of PT. Seger Agro Nusantara Dompu Branch.Keywords: job involvement, job satisfaction, turnover intention